Neurophysiological Correlates of Collective Trauma Recall in 2009 L'Aquila Earthquake Survivors. Issue 5 (19th October 2018) - Massaro, Giuseppe; Altavilla, Daniela; Aceto, Paola; Pellicano, Gaia Romana; Lucarelli, Giada; Luciani, Massimiliano; Lai, Carlo
Abstract: In the present study, we aimed to explore neural correlates of survivors of the 2009 L'Aquila, Italy earthquake in response to being shown pictures featuring their own city before and after an earthquake as well as those of an unfamiliar city. Moreover, we explored the associations among psychological variables and brain responses to the pictures of L'Aquila after the earthquake. Our final sample ( N = 30 adults) comprised 15 survivors ( M age = 31.40 years, SD = 9.42) and 15 controls ( M age = 30.53 years, SD = 10.01). Participants' electroencephalographic (EEG) data were recorded during a visual task that included earthquake‐related stimuli. Participants were assessed for posttraumatic and dissociation symptoms and event‐related potential components, and low‐resolution electromagnetic tomography (sLORETA) were analyzed. Compared to the control group, source localization in survivors indicated a lower intensity of the amygdala, hippocampal, parahippocampal, and temporopolar areas in response to visual stimuli concerning the earthquake, p < .001 to p < .0001. Results indicated a reduced limbic activation in response to visual stimuli that evoked the recall of earthquake in survivors. This finding suggests that survivors likely adopted a distancing strategy toward stimuli that may have elicited an emotional activation related to collective trauma. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Correlatos neurofisiológicos del recuerdo de un trauma colectivo en sobrevivientes del terremoto de El Águila 2009 CORRELATOS NEURONALES DEL RECUERDO DE TRAUMA COLECTIVO. En el presente estudio, quisimos explorar los correlatos neuronales de los sobrevivientes al terremoto del 2009 en Italia de la región de El Águila, en respuesta a las imágenes que muestran su propia ciudad antes y después de un terremoto, así como también las de una ciudad desconocida. Aún más, exploramos la asociación entre variables psicológicas y respuestas cerebrales a las fotos de El Águila después del terremoto. Nuestra muestra final ( N = 30 adultos) comprendía 15 sobrevivientes ( M edad = 31.40 años, DE = 9.42) y 15 controles ( M edad = 30.53, DE = 10.01). Los datos electroencefalográficos (EEG) de los participantes fueron grabados durante una tarea visual que incluyó estímulos relacionados con el terremoto. Los participantes fueron evaluados por síntomas postraumáticos y disociativos y se analizaron los componentes potenciales relacionados con el evento y tomografía electromagnética de baja resolución (sLORETA en su sigla en inglés). Comparados con el grupo control, en los sobrevivientes las fuentes localizadas indicaron una más baja intensidad para la amígdala, áreas hipo campal, parahipocampal, y témporo polar en respuesta a estímulos visuales concernientes al terremoto. Los resultados indicaron una activación límbica disminuida en respuesta a estímulos visuales que evocaban el recuerdo del terremoto en los sobrevivientes. Estos hallazgos sugieren que los sobrevivientes probablemente adoptaron una estrategia de distanciamiento hacia los estímulos que pudieran haber provocado una activación emocional relacionada con el trauma colectivo. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Neurophysiological Correlates of Collective Trauma Recall in L'Aquila 2009 Earthquake Survivors Traditional Chinese 標題: 2009年意大利拉奎拉地震生還者對集體創傷的神經生理相關因素 撮要: 本研究旨在檢視2009年意大利拉奎拉地震生還者, 對拉奎拉以及另一不熟悉的城市在地震前後的照片所產生反應的神經相關因素。我們亦檢視心理變量跟對拉奎拉地震後照片的腦部反應的關連。最終的樣本(N = 30 成人)由15名生還者(Mage = 31.40 歲, SD = 9.42)和15名對照組人士(Mage = 30.53, SD = 10.01)組成。我們在視覺實驗裡提供地震相關的刺激, 記錄樣本的腦電圖(EEG)數據。我們評估樣本的創傷後壓力症狀與離解症狀, 並分析樣本的事件相關潛在成份與低解析度電磁斷層掃描(sLORETA)。腦波來源定位反映, 生還者對地震相關的視覺刺激反應, 相比對照組, 在杏仁體、海馬體、海馬旁迴、顳極動脈區域都較弱。結果顯示, 生還者面對令他們想起地震的視覺刺激時, 邊緣系統的啟動反應會減弱。結果反映生還者大多對剌激採取保持距離的策略, 有可能使其對集體創傷有情緒啟動反應。 Simplified Chinese 标题: 2009年意大利拉奎拉地震生还者对集体创伤的神经生理相关因素 撮要: 本研究旨在检视2009年意大利拉奎拉地震生还者, 对拉奎拉以及另一不熟悉的城市在地震前后的照片所产生反应的神经相关因素。我们亦检视心理变量跟对拉奎拉地震后照片的脑部反应的关连。最终的样本(N = 30 成人)由15名生还者(Mage = 31.40 岁, SD = 9.42)和15名对照组人士(Mage = 30.53, SD = 10.01)组成。我们在视觉实验里提供地震相关的刺激, 记录样本的脑电图(EEG)数据。我们评估样本的创伤后压力症状与离解症状, 并分析样本的事件相关潜在成份与低分辨率电磁断层扫描(sLORETA)。脑波来源定位反映, 生还者对地震相关的视觉刺激反应, 相比对照组, 在杏仁体、海马体、海马旁回、颞极动脉区域都较弱。结果显示, 生还者面对令他们想起地震的视觉刺激时, 边缘系统的启动反应会减弱。结果反映生还者大多对剌激采取保持距离的策略, 有可能使其对集体创伤有情绪启动反应。